(untitled) (Asian Journal of Agriculture, 2023)
Abstract. Muljowati J, Hikam AR. 2023. Evaluation of several fungicides on mycelial growth and conidial germination of Alternaria species causing leaf spots in sunflowers under in vitro conditions. Asian J Agric 7: 47-51. Alternaria leaf spot caused by Alternaria species is the most destructive disease of sunflowers. Fungicides, such as mancozeb, carbendazim, benomyl, propiconazole, and iprodione, are commonly used to control diseases. However, the continuous use of synthetic fungicides can cause pathogen resistance to these fungicides. Therefore, the aim of this study was to conduct an in vitro test on the effect of fungicides, such as benomyl, carbendazim, mancozeb, iprodione, and propiconazole, on the mycelial growth and germination of conidia of Alternaria species causing leaf spot on sunflower. The experiment was performed in a completely randomized design with factorial patterns. The first factor was the type of fungicide, namely benomyl, mancozeb, iprodione, carbendazim, and propiconazole. The second factor was the concentration level of the (0%, 25%, 50%, 75%, 100%, and 125%) recommended dose. Data were Analyzed of Variance (ANOVA) using SPSS 18 version. The results showed that Alternaria species were resistant to carbendazim (32.98%) and benomyl (40.32%). It also shows an intermediate level of resistance to mancozeb (62.59%), iprodione (65.38%), and sensitivity to propiconazole (78.38%). Based on the research results, the authors suggest sunflower farmers use propiconazole to control Alternaria species. However, such fungicides may trigger the use of fungicides with higher doses than the recommended dose. That led to the emergence of Alternaria species resistant to the fungicides benomyl, carbendazim, mancozeb, and iprodione.